A belief in the soul may contribute to the stress experienced in the dissecting room. Issue 3 (2nd October 2013) - Martyn, Helen; Barrett, Anthony; Nicholson, Helen D.
Abstract The aim of this research was to explore whether medical students believe in a soul and how this may affect their dissecting experience. Three questionnaires were delivered electronically to the 2011 cohort of second‐year medical students over a 2‐year period. At the University of Otago, students enter medicine via three categories: Health Sciences First Year (following 1 year of university); postgraduate (following a Bachelors or higher degree); and 'other' category entry (Allied Health Professional or 3 years after a Bachelors degree). The entry category, age, ethnicity and gender of the students were collected; 51.6% of the students believed in the concept of a soul. On a scale of 1–5, students ranked the importance of religion/spirituality as 2.69. Those who believed in a soul were more likely to have a religious/spiritual component to their life and be males or 'other' category entrants. However, there were many students who believed in the soul who did not have a religious/spiritual association, suggesting that this belief extends beyond religion. Those who believed in a soul had significantly higher anticipatory stress and experienced higher levels of stress during dissection. A higher proportion of students in the 'other' category entrants believed in the concept of the soul and also had significantly higher levels of stress during dissection. Our data suggest that a belief in a soul may affect students' experiences in dissecting. Incorporating the teaching of humanities with anatomy may help medical students as they assimilate both the biomedical and philosophical aspects of dissection.